OGLE-2014-BLG-1186: gravitational microlensing providing evidence for a planet orbiting the foreground star or for a close binary source? - Dominik, Martin; Hundertmark, Markus; Schmidt, Robert W.; Tsapras, Yiannis; Wambsganß, Joachim (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. Discussing the particularly long gravitational microlensing event OGLE-2014-BLG-1186 with a time-scale tE ∼ 300 d, we present a methodology for ident